القيم الاجتماعية في الخطبة الفدكية - سالم, حنين عباس (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Value are the safety valve that stands in the face of the challenges and problems facing society, especially with the problems and challenges that the world is currently going through that are ravaging. In societies in general, perhaps the most important of these problems is the crisis of the absence of Islamic values that govern society and the trend towards values that are contrary to Islamic law, which has contributed to the emergence of problems and behaviors that are contrary to the values and customs of Islamic societies, and since social values are the main determinant of the behavior of individuals in a way that is consistent with the interest of society, the stability of social life, and service. The social system is not considered one of the tools of social control to evaluate and control the behavior of individuals and society. It is also considered one of the means of strengthening the ties between the members of one society and achieving social solidarity. It charts for individuals the correct path that they must follow in their behavior and social relations. Therefore, the research entitled ((Values) came The social values in the Fadakiya sermon ((The study of the social values included in the Fadakiya sermon. This impeccable sermon was at a high level of accuracy and depth and included many contents and sensitive topics of great importance, divine truths, rulings, legislation and Islamic values. It is an integrated approach to the right life. It was issued by... The Lady of the Women of the Worlds, the niche of prophecy and the source of the message, the stepdaughter of the Muhammadiyah school, which scholars and researchers are still devoted to transmitting in their books and research and clarifying its purposes and objectives. Therefore, this research was based on a statement of the social values contained in the Fadak sermon in order to consolidate these values in society and make them method in our lives.